217 Sleep in heavy marijuana users after smoking differing THC doses compared to controls. (3rd May 2021) - Sibai, Mohammad; Roehrs, Timothy; Koshor, Gail; Verkler, Jelena; Lundahl, Leslie
Abstract: Introduction: Sleep disturbances are commonly reported by chronic marijuana (MJ) users and often identified as reasons for MJ relapse and/or other drug use. In the current study we compared the sleep architecture of 12 heavy MJ users to 11 normal controls. Methods: Participants in the marijuana group met DSM-V criteria for cannabis use disorder but were otherwise healthy individuals. On the first study day, individuals smoked (1330-1400 hr) 11 puffs from a cannabis cigarette (7% THC). During the next four days, under varying experimental contingencies participants smoked an average of 4.58 (±3.48) day 1, 4.92 (±3.62) day 2, 4.75 (±3.52) day 3, and 4.17 (±3.56) day 4 puffs from cannabis cigarettes (7% THC). Their sleep was recorded the first four study nights using standard polysomnography procedures at Henry Ford Sleep and Research Center Hospital, under an 8-hr fixed time in bed (2300-0700 hr). Controls (n=11) had no history of illicit drug use or medical illness and were not shift workers. Neither group reported a history of sleep-related disorders. PSG recordings were scored using Rechtschaffen and Kales standard criteria. Sleep measures included sleep efficiency (total sleep time/time in bed * 100), latency to persistent sleep, and percent of time spent in Stage 1, 2, 3/4, and rapid eye movement (REM). Results: PSGs taken across all four nights of inpatient stay showed that MJ users spent significantly more time in REM sleep compared to controls (means 24.91, 24.64, 24.42, 24.13 vs 18.81, p<.001) and less time in stage 3/4 sleep (means 4.33, 4.79, 4.53, 6.91 vs 15.68, p<.001). MJ users showed reduced sleep efficiency compared to controls on night 4 (means 82.03 vs 90.32, p=0.039), and increased latency to persistent sleep on night 1 (means 6.04 vs 17.77, p=0.026). Conclusion: These data show reduced sleep efficiency, lightened sleep (reduced stage 3/4), as well as an increased duration during REM sleep in heavy MJ users during decreased use, findings that are predictive of relapse in other drug abuse populations. Support (if any): NIH/NIDA R21 DA040770 (LHL)